The effect of aspirated barium sulfate, iodixanol, and diatrizoic acid on survival and lung injury in a lagomorph model. (24th February 2017) - Siddiqui, M. Tausif; Litts, Juliana K.; Cheney, Diane M.; Kuhn, Maggie A.; Nativ‐Zeltzer, Nogah; Belafsky, Peter C.
Abstract : Objectives/Hypothesis: Contrast agents are an integral component of the video fluoroscopic swallow study. Agents commonly used include barium sulfate (E‐Z Paque), iodixanol (Visipaque), and diatrizoic acid (Gastrografin). Barium is water insoluble, whereas iodixanol and diatrizoic acid are water‐soluble iodine‐based agents. The detrimental effect of these agents on the lungs has not been systematically evaluated. Our aim was to evaluate and compare the effects of aspirated barium, iodixanol, and diatrizoic acid on pulmonary injury in a lagomorph model. Study Design: Animal model. Methods: Twenty adult male New Zealand White rabbits were divided into four groups (n = 5). Group 1 received 3 mL of barium sulfate injected into the trachea for 3 consecutive days. Group 2 received 3 mL of iodixanol injected into the trachea for 3 consecutive days. Group 3 received 3 mL of diatrizoic acid injected into the trachea for 3 consecutive days. A control group received 3 mL of air injected into the trachea under an identical protocol. All animals were euthanized on day 4, and the lung and trachea were harvested for blinded histopathologic analysis. The primary outcome measure was survival. The secondary endpoint was a blinded, histologic grading system of lung injury. Results: Two animals in the barium group, one in the diatrizoic acid group, and 0 animals in the iodixanol and control groups died. The overall lung injury score for the barium (60.60 ± 6.34) and iodixanol groups (52.30 ± 3.11) were significantly higher (worse) than the diatrizoic acid (49.60 ± 7.64) and control groups (37.80 ± 3.56) ( P < .05). Diatrizoic acid produced the least amount of lung injury. Conclusions: The data suggest that 3 mL of aspirated barium sulfate (E‐Z Paque) over 3 consecutive days causes more severe lung injury in a lagomorph model than 3 mL of aspirated iodixanol (Visipaque) and diatrizoic acid (Gastrografin). Diatrizoic acid caused the least histologic evidence of lung injury. Level of Evidence: NA Laryngoscope, 127:E148–E152, 2017